Generation and Applications of Human Pluripotent Stem Cells Induced into Neural Lineages and Neural Tissues - Martinez, Yannick; Dubois-Dauphin, Michel; Krause, Karl-Heinz (Frontiers in Physiology, 2012)
Human pluripotent stem cells (hPSCs) represent a new and exciting field in modern medicine, now the focus of many researchers and media outlets. The hype is well-earned because of the potential of stem cells to contribute to disease modeling, drug screening, and even therapeutic approaches. In this review, we focus first on neural differentiation of these cells. In a second part we compare the various cell types available and their advantages for in vitro modeling. Then we provide a “state-of-the-art” report about two major biomedical applications: (1) the drug and toxicity screening and (2) the neural tissue replacement. Finally, we made an overview about current biomedical research using differentiated hPSCs.